2008
DOI: 10.1007/s11274-008-9897-x
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose-degrading enzyme production by white-rot Basidiomycetes isolated from the forests of Georgia

Abstract: The production of lignocellulolytic enzymes by eleven basidiomycetes species isolated from two ecosystems of Georgia was investigated for the first time under submerged (SF) and solid-state fermentation (SSF) of lignocellulosic by-products. Notable intergeneric and intrageneric differences were revealed with regard to the extent of hydrolase and oxidase activity. Several fungi produced laccase along with hydrolases in parallel with growth during the trophophase, showing that the synthesis of this enzyme is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 34 publications
6
38
1
8
Order By: Relevance
“…Finally, among the carbon sources, wheat bran produced the largest enzymatic activity (1,929±44 U.L -1 ) on the eighth day of growth, a value more than 20-fold larger compared with the activity obtained using 1 mm oil palm empty fruit bunches. This is consistent with other reports in which wheat bran produced high values of enzyme activity, such as the studies in Fomes fomentarius, P. ostreatus, and Pseudotremella gibosa (Elisashvili et al, 2009).…”
Section: Optimization Of the Media Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, among the carbon sources, wheat bran produced the largest enzymatic activity (1,929±44 U.L -1 ) on the eighth day of growth, a value more than 20-fold larger compared with the activity obtained using 1 mm oil palm empty fruit bunches. This is consistent with other reports in which wheat bran produced high values of enzyme activity, such as the studies in Fomes fomentarius, P. ostreatus, and Pseudotremella gibosa (Elisashvili et al, 2009).…”
Section: Optimization Of the Media Compositionsupporting
confidence: 93%
“…The production of fungi laccases in submerged cultures has been widely reported (Stajic et al, 2006;Osma et al, 2007;Elisashvili et al, 2009). However, the constitutive expression of laccases has been low when fungi are cultured following this strategy, even using the natural substrate (Galhaup et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that, on different isolates of the same species, activity titers varied between 0.017 and 1.041 U/mL, and cellulases were not detected at all in five strains. These values are low compared to those reported by Elisashvili et al (2009), a study in which Pseudotremella gibbosa IBB22 strain was selected as the best producer with 122 U/mL. In the case of the Trametes strains assayed, varied titers from 2 to 74 U/mL were observed.…”
Section: Cs2 Uamh 8156contrasting
confidence: 60%
“…Under the culture conditions used in this study, laccase titers were notably lower. This could be due to the presence of pigments and phenolic compounds in the lignin rich-substrates used, which could inhibit laccase activity while stimulating cellulase, hemicellulose, and pectinase activities (Elisashvili et al 2009). …”
Section: Cs2 Uamh 8156mentioning
confidence: 99%
“…In the same way, microflora's potential as enzyme producers has been explored in different areas, which include: degradation of lignocellulose for fertilizers production or bioremediation of dyes (Nazareth and Sampy 2003); bio-bleaching and fibers improvement in the paper industry (Sigoillot et al 2002;Elisashvili et al 2011); and on the development of integral biorefineries using agro-industrial wastes (Elisashvili et al 2009). …”
Section: Introductionmentioning
confidence: 99%